First Approach of Fractals Nickel-Copper Dendrites on Stainless Steel Electrodes for Ammonia Oxidation to Nitrogen Monitored in Operando by Differential Electrochemical Mass Spectroscopy - Aguirre-Quintana, M; Aguirre-Quintana, M; Barrientos-Carvacho, H; Barrientos-Carvacho, H; Pizarro-Reyes, J; Pizarro-Reyes, J; Matamala-Troncoso, F (Elsevier Ltd, 2024)
Fractal nickel-copper dendrites were synthesized by electrochemical deposition (ECD) on a stainless steel electrode (SS/NiCu). The electrode surface was characterized using Field Emission Scanning Electron Microscopy (FE-SEM), X-ray diffractometry (XRD), and Raman spectroscopy. The Ni-Cu molar ratio and the time applied in the ECD method were studied, revealing that both are critical factors in modifying and controlling the surface morphology. The SS/NiCu electrodes show a higher density current response when exposed to ammonium hydroxide, reaching a limiting current density at concentrations above 0.050 M NH4OH. Ammonia oxidation reaction (AOR) was monitored in operando using differential electrochemical mass spectroscopy (DEMS). When a bias potential over +1.50 V (vs. RHE) was applied, the evolution of oxygen and NO was observed. However, N2 was the only oxidation product at a constant potential below +1.50 V (vs. RHE). Oxygen (O2) evolution was the main competitive reaction during the AOR. The results show that products are strongly dependent on the electrochemical perturbation applied. The study demonstrated that the SS/NiCu electrodes are suitable for AOR to N2 in high alkaline conditions. © 2024
Keywords: Ni dendrites; Nickel copper alloy; Stainless steel; Ammonia oxidation; DEMS